2021
DOI: 10.1186/s13063-021-05737-0
|View full text |Cite
|
Sign up to set email alerts
|

The design of a Bayesian adaptive clinical trial of tranexamic acid in severely injured children

Abstract: Background Trauma is the leading cause of death and disability in children in the USA. Tranexamic acid (TXA) reduces the blood transfusion requirements in adults and children during surgery. Several studies have evaluated TXA in adults with hemorrhagic trauma, but no randomized controlled trials have occurred in children with trauma. We propose a Bayesian adaptive clinical trial to investigate TXA in children with brain and/or torso hemorrhagic trauma. Methods/des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This is especially true for younger children as they received less frequently TXA compared with older children even if they fulfilled criteria for appropriate TXA use. The Traumatic injury clinical trial evaluating tranexamic acid in children (TIC-TOC) trial (NCT04387305), a double-blind, multicenter clinical trial, could soon provide new evidences regarding the TXA efficacy in children with brain and/or torso hemorrhagic injury (31).…”
Section: At the Bedsidementioning
confidence: 99%
“…This is especially true for younger children as they received less frequently TXA compared with older children even if they fulfilled criteria for appropriate TXA use. The Traumatic injury clinical trial evaluating tranexamic acid in children (TIC-TOC) trial (NCT04387305), a double-blind, multicenter clinical trial, could soon provide new evidences regarding the TXA efficacy in children with brain and/or torso hemorrhagic injury (31).…”
Section: At the Bedsidementioning
confidence: 99%
“…Technical aspects of our TRIPS RAR design, such as fixed placebo arm allocation and delaying RAR implementation until 180 of the target 500 patients have been enrolled, were selected to minimize inference issues with use of frequentist approaches under this design. We firmly believe that the RAR design used is appropriate for the TRIPS trial due to potential benefits in the resulting trial's ability to "efficiently" identify treatment differences (or lack thereof) between the study arms, as illustrated in the examples above and reported by others (15,22,23). When comparing individual arms to control, there is a risk of concluding a spurious finding due to random noise.…”
Section: Discussionmentioning
confidence: 99%
“…36 They plan to use a double-blind, Bayesian adaptive approach, which includes a dose-response model to help identify the ideal dosing in children. 37 With VHA and other coagulation testing, they will also evaluate the efficacy of TXA across the fibrinolytic spectrum. Hopefully, this study will provide clear evidence for the appropriate timing, dose, and patient selection for administering TXA in pediatric trauma.…”
Section: Discussionmentioning
confidence: 99%
“…To address these questions, the TIC-TOC (traumatic injury clinical trial evaluating tranexamic acid in children) collaborators have proposed an RCT evaluating the efficacy of TXA in 2,000 severely injured children with hemorrhagic brain and/or torso injuries 36 . They plan to use a double-blind, Bayesian adaptive approach, which includes a dose-response model to help identify the ideal dosing in children 37 . With VHA and other coagulation testing, they will also evaluate the efficacy of TXA across the fibrinolytic spectrum.…”
Section: Discussionmentioning
confidence: 99%